Platelets promote invasion and induce epithelial to mesenchymal transition in ovarian cancer cells by TGF-β signaling pathway - Guo, Yi; Cui, Wei; Pei, Yuqing; Xu, Danfei (Gynecologic oncology, 2019)
To test whether platelets could increase invasion potential and initiate EMT in ovarian cancer cells via a TGF-β signaling pathway. Blood samples were collected in 69 patients with ovarian cancer, 16 patients with benign ovarian tumor and 64 healthy donors. SK-OV-3 and OVCAR-3 ovarian cancer cells were treated with platelets. Transwell assays were used to analyze the invasive capacity, and EMT was assessed by microarray analysis, quantitative real-time PCR (qPCR) and Western blotting. Activation of TGF-β pathway was examined by ELISA and Western blotting. TGF-β type I receptor (TβR I) inhibitor A83-01 was used to confirm the role of TGF-β pathway in vitro and in vivo. Clinical data showed ovarian cancer patients with elevated platelet counts had a higher incidence of advanced stages. Treatment with platelets increased the invasive properties of both cell lines. Mesenchymal markers (snail family transcriptional repressor-1, vimentin, neural cadherin, fibronectin-1 and matrix metalloproteinase-2) were up-regulated in platelet-treated cells, while the epithelial marker (epithelial cadherin) was down-regulated. Higher TGF-β level was observed in patients with elevated platelet counts when compared to the subjects. Higher levels of TGF-β were also found in culture medium treated with platelets, and cells treated with platelets also showed increased phosphorylation of Smad2. TβR I inhibitor A83–01 reversed the EMT-like alterations and inhibited platelet-induced invasion in vitro and in vivo. Platelet increased invasion potential and induced EMT in ovarian cancer cells in a TGF-β dependent pathway. Platelet-derived TGF-β may be useful as a new target treatment for ovarian cancer. •Ovarian cancer patients with elevated platelets showed higher incidence of metastasis.•Platelets increase invasive ability and induce EMT in ovarian cancer cells.•Serum TGF-β level was higher in ovarian cancer patients with elevated platelet.•TGF-β/Smad pathway was activated in platelet-treated ovarian cancer cells.•TGF-β type I receptor inhibitor A83-01 abolished platelets-induced invasion and EMT in vitro and in vivo.